Minimal dualism and epistemic approach - B. V. Faul (Омский научный вестник: Серия "Общество. История. Современность")
In this paper the author presents an argument in favor of minimal dualism — thesis, according to which conscious agents are able to exist without bodies. Author demonstrates the advantages of this argument. Firstly, he shows that this argument is invulnerable to the epistemic strategy of criticizing the conceivability argument. Secondly, the epistemic approach restricts the conceivability of creatures, the possibility of which is incompatible with the minimal dualism